Exploring the prevalence and profile of epilepsy across Europe using a standard retrospective chart review: Challenges and opportunities. (2nd September 2021) - Linehan, Christine; Benson, Ailbhe; Gunko, Alex; Christensen, Jakob; Sun, Yuelian; Tomson, Torbjorn; Marson, Anthony; Forsgren, Lars; Trinka, Eugen; Iliescu, Catrinel; Althoehn Sonderup, Julie; Werenberg Dreier, Julie; et al.
Summary: Objective: This study aimed to determine the prevalence of epilepsy in four European countries (Austria, Denmark, Ireland, and Romania) employing a standard methodology. The study was conducted under the auspices of ESBACE (European Study on the Burden and Care of Epilepsy). Methods: All hospitals and general practitioners serving a region of at least 50 000 persons in each country were asked to identify patients living in the region who had a diagnosis of epilepsy or experienced a single unprovoked seizure. Medical records were accessed, where available, to complete a standardized case report form. Data were sought on seizure frequency, seizure type, investigations, etiology, comorbidities, and use of antiseizure medication. Cases were validated in each country, and the degree of certainty was graded as definite, probable, or suspect cases. Results: From a total population of 237 757 in the four countries, 1988 (.8%) patients were identified as potential cases of epilepsy. Due to legal and ethical issues in the individual countries, medical records were available for only 1208 patients, and among these, 113 had insufficient clinical information. The remaining 1095 cases were classified as either definite ( n = 706, 64.5%), probable ( n = 191, 17.4%), suspect ( n = 153, 14.0%), or not epilepsy ( n = 45, 4.1%). Significance: Although a precise prevalence estimate could not be generated from these data, the study found a high validity of epilepsy classification among evaluated cases (95.9%). More generally, this study highlights the significant challenges facing epidemiological research methodologies that are reliant on patient consent and retrospective chart review, largely due to the introduction of data protection legislation during the study period. Documentation of the epilepsy diagnosis was, in some cases, relatively low, indicating a need for improved guidelines for assessment, follow‐up, and documentation. This study highlights the need to address the concerns and requirements of recruitment sites to engage in epidemiological research.